Titanium dental implant surfaces - Elias,Carlos Nelson (2010)
Osseointegration has been defined as "a direct structural and functional connection between ordered, living bone and the surface of a load-carrying implant". However, titanium and its alloys cannot directly bond to living bone after being implanted into the body. The osseointegration of titanium dental implants is critically dependent on the implant surface properties. Various surface modifications have been proposed in order to provide commercially pure titanium with bioactive bone bonding ability. In the present work, the titanium dental implant surface morphology was modified by acid etching and electrochemical treatments with the purpose of enhancing tissue response, and decreasing the waiting time for implant loading. The results show that surface morphology, topography, roughness and chemical composition were changed by the treatments and these changes has a significant influence on osseointegration. The best results were observed in the samples submitted to the electrochemical treatment.